CT Guided FNAC of lung mass – A retrospective study of Disease Spectrum - Singh, Rashmi; Mallik, Mahasweta; Rai, Hari Kishore; Singh, Shweta; Mallick, Sujata; Kumar, Manish (International Journal of Medical Research and Review, 2016)
CT guided FNAC is a well established method in the cytological diagnosis of pulmonary lesion. Aim: Aim of our study is to evaluate the pathological spectrum of disease in lump through CT guided FNAC. Material & method: 69 causes were evaluated retrospectively for a period of 4 yrs. Result: out of 69 cases 52.1% were male. Mean age was 54. 34 years. 65.2% having malignant lesion & 34.7% have benign. Adeno CA was the predominant malignant tumour. Conclusion: CT guided FNAC can diagnose pulmonary lesion fairly accurately leading to less morbidity & mortality as treatment can be started early.